Carbohydrate ingestion attenuates the increase in plasma interleukin-6, but not skeletal muscle interleukin-6 mRNA, during exercise in humans - Starkie, R L (Blackwell Science Inc, 2001)
1. The present study was undertaken to examine the effects of exercise and carbohydrate (CHO) ingestion on interleukin-6 (IL-6) gene expression in skeletal muscle and plasma IL-6 concentration. 2. Seven moderately trained men completed 60 min of exercise at a workload corresponding to each individual's lactate threshold on four randomised occasions. Two trials were conducted on a bicycle ergometer (Cyc) and two on a running treadmill (Run) either with (CHO) or without (Con) the ingestion of a CHO beverage throughout the exercise. Muscle biopsies were obtained from the vastus lateralis before and immediately after exercise and IL-6 gene expression in these samples was determined using real-time PCR. In addition, venous blood samples were collected at rest, and after 30 min during and at the cessation of exercise. These samples were analysed for plasma IL-6. 3. Irrespective of exercise mode or CHO ingestion, exercise resulted in a 21 ± 4-fold increase (P < 0.01; main exercise effect) in IL-6 mRNA expression. In contrast, while the mode of exercise did not affect the exercise-induced increase in plasma IL-6, CHO ingestion blunted (P < 0.01) this response. 4. These data demonstrate that CHO ingestion attenuates the plasma IL-6 concentration during both cycling and running exercise. However, because IL-6 mRNA expression was unaffected by CHO ingestion, it is likely that the ingestion of CHO during exercise attenuates IL-6 production by tissues other than skeletal muscle.